2012
DOI: 10.1080/15685551.2012.747145
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydrocarbon polymers by cationic polymerization and their thermal properties

Abstract: Cationic homo-and co-polymerization of indene (Ind), styrene (St), limonene (Lim), and 5-ethylidene-2-norbornene (ENB) was performed with AlCl 3 in dichloroethane at À20°C under inert N 2 . The aim of this work is to investigate the effect of the reaction conditions on the molecular weight of polyindene (PInd) obtained by cationic polymerization with AlCl 3 without an electron donor, and also to determine the effect of the use of cyclic diolefin comonomers on the polymer properties. The polymers were synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
4
21
0
4
Order By: Relevance
“…The peaks of the –OCH 2 group for BA are located at ∼4.0 ppm; the peaks for the limonene endocyclic and exocyclic double bonds are located at 5.4 and 4.7 ppm, respectively. As the endocyclic double bond of limonene is very stable, it is a reasonable assumption that only the exocyclic double bonds participated in the polymerization, whereas the endocyclic double bonds remained in the polymer chain. Thus, the following equation was used to calculate copolymer composition: BA%=A4.02A4.02+A5.4 where A 4.0 refers to the peak area at δ = 3.8–4.2 which corresponds to the –OCH 2 –protons of BA (“D” in Figure ), and A 5.4 refers to the endocyclic double bond of limonene (“a” in Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks of the –OCH 2 group for BA are located at ∼4.0 ppm; the peaks for the limonene endocyclic and exocyclic double bonds are located at 5.4 and 4.7 ppm, respectively. As the endocyclic double bond of limonene is very stable, it is a reasonable assumption that only the exocyclic double bonds participated in the polymerization, whereas the endocyclic double bonds remained in the polymer chain. Thus, the following equation was used to calculate copolymer composition: BA%=A4.02A4.02+A5.4 where A 4.0 refers to the peak area at δ = 3.8–4.2 which corresponds to the –OCH 2 –protons of BA (“D” in Figure ), and A 5.4 refers to the endocyclic double bond of limonene (“a” in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Limonene (C 10 H 16 ) is an unsaturated cyclic hydrocarbon which possesses two non‐conjugated double bonds: an endocyclic double bond and an exocyclic double bond, both of which provide potential for polymerization (see Figure (a)). However, because of the ring strain energy and steric impediments, the endocyclic double bond of limonene shows a much lower reactivity than the exocyclic vinyl group during polymerization . The polymerization of limonene has been studied since the 1950 s .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that limonene has a high propensity toward chain‐transfer reactions, as the allylic hydrogens next to the double bonds are very reactive and tend to be easily captured by living radicals . During polymerization, molecular weight development is greatly influenced by this chain‐transfer reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…62 The polymerisation of 6 was first carried out by Roberts and Day 37 by using Friedel-Crafts conditions; early attempts were capable of producing only lowmolecular weight polymers. The cationic polymerisation of limonene (6) using AlCl 3 as a catalyst was studied by Brum et al 63 The poly(limonene) (32) (Scheme 5) produced had a very low molecular weight (c. 0·5 kDa), and low conversions of only 7% were achieved; this is likely attributed to chain termination by way of b-elimination. Satoh et al 64 were able to synthesise a …”
Section: 3mentioning
confidence: 99%